Benefits of recreational dance and behavior analysis for individuals with neurodevelopmental disorders: A literature review. (5th September 2020) - Pontone, Madeline; Vause, Tricia; Zonneveld, Kimberley L. M.
Abstract: Dance can be an entertaining experience that offers multiple benefits for those who participate. Unlike typically developing populations, studies examining benefits of recreational dance for individuals with neurodevelopmental disorders are limited. In this review, we conducted a literature search, where "dance" was cross‐listed with all neurodevelopmental disorders across five databases, yielding 19 articles. Twelve studies involved children and youth with neurodevelopmental disorders aged 3–19 years, two studies included both adolescents and adults aged 14–22 years, and five studies included adults aged 20–65 years. Given the effectiveness of applied behavior analysis in enhancing skill development, it is encouraging that eight studies explicitly identified behavioral components. Results suggest potential benefits of recreational dance across studies using self‐report and objective measures, but limited research with sound methodology exists. There is a need for controlled research with measurable outcomes to evaluate programs tailored to these populations to improve core challenges and secondary outcomes such as quality of life.